Eruption conversations with Eddie Van Halen - Tolinski, Brad; Gill, Chris (Hachette Books, 2021)
The life of the late groundbreaking musician is recalled through over fifty hours of interviews and delves both into his musical legacy as well as his lifelong issues with social anxiety and substance abuse
Keywords: Van Halen, Eddie -- 1955-2020; Van Halen, Eddie / 1955-2020; Van Halen, Eddie / 1955-2020 / Interviews; Guitarists / United States / Biography; Guitarists / United States / Interviews; Rock musicians / United States / Biography; Rock musicians / United States / Interviews; BIOGRAPHY & AUTOBIOGRAPHY / Music; MUSIC / Genres & Styles / Rock; MUSIC / Genres & Styles / Heavy Metal; Guitarists; Rock musicians; United States; Biographies; Interviews; Interview; Biografie